PENGEMBANGAN MEDIA PEMBELAJARAN FISIKA SMA MATERI HUKUM NEWTON TENTANG GERAK MENGGUNAKAN MACROMEDIA FLASH 8 - Putri, Shinta Ardani; Azhar, Azhar; Nasir, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to produce high-school physics learning media Newton's legal material about valid motion so it is worthy to be used as a medium for learning physics of high school students. The research method used is research and development with development stage following the ADDIE model. Media developed through three stages in accordance with the development model used. In this study, the media was developed only until at the 3rd stage of the 5 stages of the ADDIE model of analysis, design and devolepment. The research data obtained from the validation of 6 experts as a validator. The validation instrument in adaptation of Nasir 2014 is composed of 4 aspects, namely design aspect, pedagogic aspect, content aspect and technical aspects. Design aspect of 3.85 in the high category, aspect paedagogik equal to 4,0491 in high category, content aspect of 3,92 in high category and technical aspect equal to 3,95 in high category. Overall, each assessment indicator on each aspect is declared valid and in accordance with the development objectives. Based on this matter, it can be concluded that the physics learning media has been valid based on design aspect, pedagogic aspect, content aspect and technical aspect so it is worthy to be used as a source of high school physics on Newton's legal matter about motion. Keywords: Newton's Law, Computer Media, High School Physics